2022
DOI: 10.3389/fnut.2022.880488
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis EEAM 10B Strengthens Nutrient Metabolic Process in Black Soldier Fly Larvae (Hermetia illucens) via Changing Gut Microbiome and Metabolic Pathways

Abstract: Insects are a potential alternative protein source to solve the food shortage crisis. Previous studies have illustrated that probiotics can improve the substrate conversion efficiency of insects and increase insect protein content. However, the effects of probiotics on insect physiology and nutrient metabolism are still not well understood. Here, the black soldier fly larvae (BSFL), Hermetia illucens (Diptera: Stratiomyidae), was used as a study subject to deeply investigate the specific interaction among a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Indeed, insect gut microbiota can be considered an additional organ with fluidity or malleability. The larval intestinal microbiota is a crucial contributor to the BSFL nutrient metabolic process [ 22 ] and helps the host to tolerate heavy metals [ 29 ] and degrade antibiotics [ 30 , 31 ]. Lou et al [ 30 ] identified two bacterial strains— Alcaligenes faecalis GLD-1 and Ochrobactrum intermedium GLD-2—capable of degrading lincomycin from BSFL gut.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, insect gut microbiota can be considered an additional organ with fluidity or malleability. The larval intestinal microbiota is a crucial contributor to the BSFL nutrient metabolic process [ 22 ] and helps the host to tolerate heavy metals [ 29 ] and degrade antibiotics [ 30 , 31 ]. Lou et al [ 30 ] identified two bacterial strains— Alcaligenes faecalis GLD-1 and Ochrobactrum intermedium GLD-2—capable of degrading lincomycin from BSFL gut.…”
Section: Discussionmentioning
confidence: 99%
“…Functional bacteria isolated from the BSFL gut have been found to benefit the growth of BSFL. Pei et al [ 22 ] reported that Bacillus velezensis EEAM 10B could improve the protein synthesis process and digestive enzyme activities in BSFL, thus elevating the substance uptake and protein conversion ability of BSFL. When the intestinal ciprofloxacin-degrading isolates were re-inoculated to the sterile BSFL system, the larvae survival rate and weight were significantly increased in comparison with the sterile BSFL system [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, diets consisting of lignocellulolytic biomass have demonstrated poor conversion into larval mass [ 32 ]. Thus, it is not unexpectedly that materials such as soybean curd residue [ 36 ], rice straw [ 34 ], and peanut shell powder [ 47 ] are included in studies to stimulate insect productivity. At the same time, as summarized in Table 1 , many studies were performed on (chicken) manure as BSFL have been opted as a valuable solution for these types of waste to reduce ecological pollution [ 10 ].…”
Section: Set-up Of Inoculation Trials For Bsfl Rearingmentioning
confidence: 99%
“…BSFL has been used to degrade organic waste. Most of the omics data used to study the changes of gut microbiota composition involve 16S rRNA or 16S rDNA ( Jiang et al, 2019 ; Wynants et al, 2019 ; Zhan et al, 2020 ; Pei et al, 2022 ). Few studies have focused on ITS1 sequence changes.…”
Section: Introductionmentioning
confidence: 99%